Application of Integrated Project-based and STEM-based E-learning Tools to Improve Students’ Creative Thinking and Self-Regulation Skills - Molani Paulina Hasibuan; Ratih Permana Sari; Ricky Andy Syahputra; Nahadi Nahadi (Postgraduate, University of Mataram, 2022)
In today's digital environment, using technology in learning is a requirement for staying relevant to the needs of the twenty-first century. The goal of this study is to develop learning tools that combine Project-based learning (PjBL) with STEM-based e-learning to assist students enhance their creative thinking skills and self-regulation. This study is a quantitative descriptive study using a one-shot case study research design and a research sample of 25 high school students in class for the academic year 2020/2021. The N-Gain score is used to collect data using test and non-test instruments before and after treatment to assess if there is an improvement in learning outcomes. All indicators of critical thinking skills and self-regulation increased as a result of the study. On the fluency indicator, the creative thinking skills indicator received the highest score of 0.86, while self-regulation received the biggest rise on the organizing and transforming indicator with a score of 0.83. The average increase in critical thinking skills is 73.66 percent, and the average rise in self-regulationÂ is 79.42 percent, both of which are high